2015
DOI: 10.1111/chd.12303
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity Long-Term after Arterial Switch Operation for Transposition of the Great Arteries

Abstract: Our results showed that exercise capacity long-term after ASO in TGA is well preserved although lower than in healthy children what might be explained by the presence of chronotropic incompetence in the TGA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
13
1
1
Order By: Relevance
“…The long-term clinical effect of increased RV afterload in ASO patients warrants life-long monitoring. Arterial switch operation patients generally demonstrate normal RV ejection fraction 4 ; however, their exercise capacity is at least borderline low compared to the normal population, [28][29][30] and exercise limitation has been correlated with smaller PA sizes and maldistribution of pulmonary blood flow. 31,32 Subtle impairments in RV function also persist after surgical repair, such as decreased RV free wall strain and decreased systolic/diastolic tissue Doppler imaging velocities.…”
Section: Commentmentioning
confidence: 99%
“…The long-term clinical effect of increased RV afterload in ASO patients warrants life-long monitoring. Arterial switch operation patients generally demonstrate normal RV ejection fraction 4 ; however, their exercise capacity is at least borderline low compared to the normal population, [28][29][30] and exercise limitation has been correlated with smaller PA sizes and maldistribution of pulmonary blood flow. 31,32 Subtle impairments in RV function also persist after surgical repair, such as decreased RV free wall strain and decreased systolic/diastolic tissue Doppler imaging velocities.…”
Section: Commentmentioning
confidence: 99%
“…The overall long-term outcomes of Transposition of the Great Arteries patients have been described as excellent, 26 although lower longterm exercise capacity has been observed in some Transposition of the Great Arteries patients due to the presence of a chronotropic incompetence. 27 A Ventricular Septal Defect is normally closed in early childhood and children are post-surgically considered healthy and fit. However, it has been described that young adults with surgically corrected Ventricular Septal Defect have reduced cardiopulmonary exercise capacity and significantly lower physical functioning scores compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up after delivery, no woman showed deterioration of NYHA functional class or systemic ventricular dysfunction, with the exception of increased pulmonary or aortic regurgitation in 2 cases. Several authors reported that ASO survivors show better cardiac function, exercise performance, self-reported quality of life, and fewer somatic complaints compared to Mustard patients [8,21,7]. Because the systemic ventricle was corrected to the left ventricle, physiological loads such as pregnancy may have a reduced adverse impact on cardiac function in women after ASO, compared to a systemic right ventricle such as in the atrial switch group.…”
Section: Prognosis After Deliverymentioning
confidence: 99%
“…The progression to ASO had positive impact on systemic ventricular function, morbidity, and exercise capacity long-term follow-up [7,8]. The systemic left ventricle could be treated with better mid-and long-term outcomes, compared to the systemic right ventricle.…”
Section: Introductionmentioning
confidence: 99%